Literacy Practices of Indonesian College Students Participating in One Semester Off-Campus Program - Nafisah, Raudhatun; Syahrani, Rizky Amalia; Parlindungan, Firman; Khairi, Alfin (Linguists : Journal of Linguistics and Language Teaching, 2024)
Although there is a growing consensus in research that literacy practices can inform growth in literacy competence, there remains a dearth of studies explaining what and how Indonesian college students interact with texts in off-campus contexts. The objectives of this study are two folds: (1) to identify types of literacy practices carried out by Indonesian undergraduate students; and (2) to study the differences in use of the literacy practices between high rating and low rating students. As many as 200 Indonesian undergraduate students participated in this study. They were asked to complete an online questionnaire of literacy practices and a self-assessment. Principal Component Analysis were employed to analyze data for the first research question. T-test analysis was performed to answer the second research question. We found that there are 8 factors treated as posteriori categories of students’ literacy practices off campus, including professional-related literacy practices, academic-related literacy practices, knowledge-generating literacy practices, self-regulated literacy practices, leisure literacy practices, transactional literacy practices, and course-related literacy practices.. The t-test analysis showed that there are significant differences in use of literacy practices in the four first factors between high rating and low rating students. This is because high rating students typically engaged in reading and writing activities that support success of their college program. These findings indicate that determining effective interventions is pivotal to improve literacy skills of Indonesian college students that tap into their structure of literacy practices out of campus.